How to Transform a Perforator Propeller Flap into a Keystone Flap in Case of Unsatisfying Perforator Vessel Local Perforator Flap Coverage in Limbs - Elena Ciucur; Hadj Boukhenouna; Benjamin Guena; I. Garrido-Stowhas; Christian Herlin; Benoit Chaput (Archives of Plastic Surgery, 2023)
Moderate soft-tissue defects need stable coverage, ideally with tissue of similar characteristics and low donor site morbidity. We propose a simple technique for the coverage of moderate skin defects in the limbs. It allows intraoperative transformation of a propeller perforator flap (PPF) into a keystone design perforator flap (KDPF) in cases of unsatisfying perforator vessel or in cases of unpredictable intraoperative events. Between March 2013 and July 2019, nine patients with moderate soft-tissue defects (mean defect size 4.5 × 7.6 cm) in the limbs (two on the upper limbs and seven on the lower limbs) were covered using this technique. We performed four PPFs and five KDPFs. The mean follow-up was 5 months. There was one complication, partial distal tip necrosis in a PPF located in the leg, which healed by secondary intention within 3 weeks. The donor site was closed directly in all cases. No functional impairments were noted regardless of the perforator flap utilized. This technique enables us to employ flexible surgical strategies and allows us to make adjustments based on the patient's vascular anatomy.